Нові давньоруські пам’ятки на Нижньому Тетереві - Чміль, Л.В.; Козюба, В.К. (Археологія і давня історія України, 2020)
У статті подано коротку характеристику давньоруських пам’яток, розташованих на берегах нижньої течії р. Тетерев. За останнє десятиліття автори й інші дослідники обстежили 15 поселень, з 22 відомих на цій території. Більше половини поселень (12) розташовані на підвищеннях у заплавах Тетерева і Здвижа, що засвідчує перспективність пошуку середньовічних пам’яток на інших ділянках долин цих річок. The paper is the brief description of the Old Rus sites situated on the Lower Teteriv River banks. Still recently that area was one of the poor studied regions of the Kyiv Polissia area. According to the 19th century sources there were 2 medieval hill-forts here. 13 settlements of the 10th—13th centuries were found on the territory of Ivankiv region in the 20th century. During the last decade the authors and other researchers have inspected 15 of the 22 settlements known in that area. The most of them were discovered first.